Molecular and Immunological Evaluation of Some Bacteria Causing Calf Diarrhea - Alsadik, Gehan M.; Atia, Noha M.A.; Elrafie, Amira Samir; Rasheed, Neveen A. (Journal of Advanced Veterinary Research, 2023)
One issue that intensive farming has to deal with is neonatal calf diarrhea, and probiotics are seen to be a viable solution to improve the health of calves. The aim of this study was to assess the effects of short-term administration of an antibiotic or probiotic to diarrheal calves on total leukocytic count, serum bactericidal activity, and phagocytosis, as well as to identify potential bacteria that may cause calf diarrhea in early life stages. 55 diarrheal calves, ranging in age from 1 to 20 days, were sampled for feces at a private dairy farm in the Sharkia governorate. E. coli, Salmonella spp., and Clostridium species were among the isolated bacteria, with prevalence rates of 58.2%, 8%, and 12%, respectively. The O26, O111, O119, O128 and O125 serogroups of E. coli isolates were the identified serotypes. While S. Typhimurium and S. Enteritidis were the recovered Salmonella serotypes. The results of the polymerase chain reaction (PCR) showed that the invA gene was amplified in the four salmonella isolates but the phoA gene was amplified in all E. coli isolates. Since only the alpha toxin gene was present in each isolate of C. perfringens, they were all type A. Antibiogram test results showed that most isolated species were multi-drug resistant to the ten commonly used antibiotics. On the other hand, isolates of E. coli, salmonella, and clostridium that demonstrated sensitivity for amoxicillin with percentages of 93.3%, 100%, and 66.7%, respectively, represented the medicine that was most successful. Regardless of infection, probiotic or antibiotic treatment, the total leukocytic count values in all diarrheal calves were considerably greater than those in the control group. Serum bactericidal activity in probiotic-treated calves was significantly higher than in the control and antibiotic-treated groups, while it was significantly lower in the antibiotic-treated group. Calf polymorphonuclear leukocytes treated with antibiotics or probiotics had considerably increased phagocytic activity than the control group. In conclusion, probiotics supplementation is an effective strategy for the prevention and control of calf diarrhea.